A Pesca e o Centro de Lançamento de Alcântara: saberes e conflitos sociais - Alves, Tacilvan Silva. (2018)
In the aforementioned work, I dealt with the situation of conflicts experienced by social agents on the coast of Alcântara in the face of constant social tensions, caused by the implantation of the Lançamento de Foguetes de Alcântara – CLA, occurred in the 1980's. Faced with these impasses, I sought to construct the work evidencing the mobilizations of self-appointed fishermen who have in their daily practices the possibility of establishing their social organizations and guarantee their autonomy.I take into account that in this ethnic territory, fishing is not dissociated from different activities such as farming, hunting, raising animals and extractive activities. In addition, collective agreements are established in this local logic of common use of these natural resources that ensure the physical, social, economic and political reproduction of the group. I emphasize that the field research focused on one of the 12,000- hectare communities, the Comunidade Quilombola de Brito, is not isolated from a consolidated network of established social relations with the rest of the ethnic territory. In this sense, it was necessary to describe how the circulation of products and services inherent in the practices were made by social agents. The field research in Brito has shown that fishing is circumscribed by specificities of knowledge and practices that distinguish it from the wider economic system. and their perceptions about the natural resources and proper designations of the instruments used in the different fishing activities, that the agricultural and fishing calendars constitute these knowledges. Finally, I present a reflection about the struggle of the social agents for the permanence on the coast that appear in the different modes as they seek to reorganize their practices.